Australia Farewell: Predictors of Emigration in the 2000s - Richard V. Burkhauser; Markus Hahn; Matthew Hall; Nicole Watson (Institute for the Study of Labor (IZA), 2016)
The factors leading individuals to immigrate to developed nations are widely studied, but comparatively less is known about those who emigrate from them. In this paper, we use data from a nationally representative cohort of Australian adults to develop longitudinal measures of emigration and to assess how social ties and individual economic position predict emigration. Cox proportional hazards models indicate that the propensity to emigrate is particularly pronounced for those with relatively little social connectedness in Australia. Specifically, our results show that first-generation Australians, especially those with relatively short durations in the country, have substantially higher emigration rates than later-generation Australians. Similarly, having a partner with deeper generational roots in Australia strongly reduces the likelihood to emigrate. At the same time, our analysis also shows that economic position matters, with the not employed having higher risks of emigration. Perhaps most interestingly, estimates from our models reveal that those with university degrees are much more likely to emigrate than individuals with lower levels of education; a finding that is true for both first- and later-generation Australians.
Keywords: J1; J6; 330; Australian demography; immigration; emigration; HILDA data; Cox proportional model